Al Hisbah in Modern Era : Investor Protection Institution in Indonesian Islamic Capital Market - Sholikah, Mar'atus; Huda, Nurul; Rini, Nova; Fatwa, Nur; Wiliasih, Ranti (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to explore the evolution of the role of al hisbah in the financial sector, especially the capital markets industry. Along with the times and the increasing complexity of today's government bureaucracy, the role of al hisbah has been formed differently in each country according to their respective needs. This research uses an exploratory qualitative method with secondary data. The research results show that the role of al hisbah is very complex, one of which is in the financial sector of the capital market to carry out supervision in order to protect investors from both external and internal risks. In this case, the Financial Services Authority (OJK) plays the role of al hisbah which coordinates with the National Sharia Council (DSN) to ensure transactions and activities in the Indonesian Islamic capital market are safe and healthy.